A novel synthetic microfiber with controllable size for cell encapsulation and culture. Issue 14 (21st March 2016) - Wu, Fang; Ju, Xiao-Jie; He, Xiao-Heng; Jiang, Ming-Yue; Wang, Wei; Liu, Zhuang; Xie, Rui; He, Bin; Chu, Liang-Yin
Abstract : A novel synthetic microfiber for cell encapsulation and culture via a rapid and mild crosslinking reaction in microfluidic devices. Abstract : A facile and controllable microfluidic strategy is developed to fabricate synthetic microfibers of crosslinked 4-arm polyethylene glycol with maleimide end groups (PEG–4Mal) for cell encapsulation and culture with high viability. The gelling condition in this strategy is mild for cell encapsulation and the crosslinking process is rapid, thus guaranteeing the high viability of encapsulated cells. The diameters of PEG–4Mal synthetic microfibers are precisely adjustable by simply changing the flowrates of the inner and outer fluids in microfluidic devices. The prepared PEG–4Mal synthetic microfibers possess excellent permselectivity, which could not only guarantee the normal metabolism of encapsulated cells but also provide immunoisolation for encapsulated cells. MC3T3 cells and NIH3T3 cells are successfully encapsulated into the PEG–4Mal synthetic microfibers, and the formed microfibers enable high viability for cell encapsulation and culture. The proposed PEG–4Mal synthetic microfibers show great potential as efficient cell encapsulation systems for many potential biomedical applications in cell culture, cell therapy and tissue engineering.